Proton therapy in paediatric oncology: an Irish perspective - Lee, K. A.; O'Sullivan, C.; Daly, P.; Pears, J.; Owens, C.; Timmermann, B.; Ares, C.; Combs, S. E.; Indelicato, Daniel; Capra, Michael (Irish Journal of Medical Science, 2017)
Background: Proton therapy (PT) is a radiotherapy treatment modality that uses protons, rather than conventional photons. PT is often used in paediatric oncology due to its reported capability to reduce acute and late adverse treatment effects. As PT is unavailable in Ireland, patients are referred abroad for treatment. Aims: To: (1) produce a descriptive study of Irish children referred abroad for PT, and (2) discuss the case for PT in general. Methods: A retrospective review of all children referred for PT before October 2015 was performed. Information was gathered regarding demographics, diagnosis, referral timeline, adverse effects attributable to PT, current status and cost. A review of the relevant literature was performed. Results: Seventeen children treated in Ireland have been referred abroad for PT. The largest number was in the 0–4 year old group. At initial diagnosis the median age was 4.8 years. The average cost per child was €37,312. Two patients suffered disease relapse. Four have encountered PT-related adverse effects. Conclusion: Despite the fact that >100,000 patients worldwide have been treated with PT, the level of published evidence to support superiority over conventional treatment remains low. It is debated that randomised control trials in this area would be inconsistent with the principle of clinical equipoise. In contrast, there is a call for level 1 evidence to justify drastic changes in patient care, particularly in light of recent reports of unexpected toxicities. In time, careful evaluation, follow-up and clinical trials will likely support the preferential use of PT in children.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ethics; Paediatric oncology; Particle therapy; Proton beam therapy; Research methods